2020
DOI: 10.32014/2020.2518-1491.67
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Liposoluble Extract of Spiraea Hypericifolia L.

Abstract: News of the Academy of sciences of the Republic of Kazakhstan 2 NAS RK is pleased to announce that News of NAS RK. Series of chemistry and technologies scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The major biologically active compounds of the leaves of S. hypericifolia were flavonols and catechins, whose levels reached 32.6 and 1.8 mg/g, respectively [8]. By contrast, according to research by A.A. Kudaibergen et al [3], the concentration of flavonoids in the underground part of S. hy- Our results on the concentrations of biologically active compounds in the extract from the aerial part of S. hypericifolia are partially consistent with the literature data. For instance, in separate analyses of the bark, stems, leaves, and root cores of S. hypericifolia, N.D. Storozhenko [8] found that the main biologically active compounds in the organs of the aboveground and underground parts of the plant are flavonoids: flavonols, flavans, and flavones.…”
Section: Levels Of Biologically Active Compounds In the S Hypericifol...mentioning
confidence: 89%
See 2 more Smart Citations
“…The major biologically active compounds of the leaves of S. hypericifolia were flavonols and catechins, whose levels reached 32.6 and 1.8 mg/g, respectively [8]. By contrast, according to research by A.A. Kudaibergen et al [3], the concentration of flavonoids in the underground part of S. hy- Our results on the concentrations of biologically active compounds in the extract from the aerial part of S. hypericifolia are partially consistent with the literature data. For instance, in separate analyses of the bark, stems, leaves, and root cores of S. hypericifolia, N.D. Storozhenko [8] found that the main biologically active compounds in the organs of the aboveground and underground parts of the plant are flavonoids: flavonols, flavans, and flavones.…”
Section: Levels Of Biologically Active Compounds In the S Hypericifol...mentioning
confidence: 89%
“…The major biologically active compounds of the leaves of S. hypericifolia were flavonols and catechins, whose lev-els reached 32.6 and 1.8 mg/g, respectively [8]. By contrast, according to research by A.A. Kudaibergen et al [3], the concentration of flavonoids in the underground part of S. hypericifolia is 53.6 mg/(g of total extract), while their concentration in the aboveground part does not exceed 7.7 mg/g. The discrepancy in the results is possibly due to the fact that the accumulation of these substances is influenced by environmental factors associated with the ontogenetic state of the plant at the time of sampling of the plant material; another possible reason is the choice of methods for analyzing the extracts.…”
Section: Levels Of Biologically Active Compounds In the S Hypericifol...mentioning
confidence: 91%
See 1 more Smart Citation